ANALISIS KUALITAS WEBSITE E-OFFICE ATR/BPN KOTA PALEMBANG MENGGUNAKAN METODE MCCALL - Rachma Octadiani Putri; Nyimas Sopiah; Andri; Siti Sauda (P3M Institut Teknologi Pagar Alam, 2023)
This research measures the level of the Palembang City ATR/BPN E-Office website using the McCall method. The McCall method is one method that can be used to measure software quality. Based on the researcher's interview with one of the Palembang City Land Office staff who said that the website was still not up to date in conveying information and lacked responsiveness or speed in accessing the website so they had to wait a long time (less efficient) where no one had ever measured the quality of the website. In this research, the McCall method is used, where analyzing website quality is based on 5 factors in product operation, namely correctness, reliability, efficiency, integrity and usability. The results of this research in the form of percentage results from the distribution of questionnaires from respondents were tested for validity and reliability values in order to obtain valid and reliable variables and indicators that were used as measuring tools in this research. The variables and indicators that are valid and reliable are then used to measure the quality value (Fa) of each variable. Measurement begins with the process of weighting variables and indicators through a questionnaire filled out by 3 experts at the Palembang City Land Office. Value weighting is carried out using a scale of 0.1 to 0.4 for each variable of truth, reliability, efficiency, integrity and use along with their respective indicators. The results of calculating the total quality level of the Palembang City ATR/BPN E-Office website show a percentage value of 68% which is in the range of 61-80%, which means it is in the Good category.